Anomaly of Coeliaco-Mesenteric Axis: A Rare Arterial Variation - Arindom Banerjee; Anirban Das Gupta; I. Anil Kumar; M. Pranay Kumar; P. Jhansi Laxmi (Journal of Clinical and Diagnostic Research, 2012)
While doing a routine dissection in an 85 years old cadaver, it was observed that instead of a single coeliac trunk, two trunks originated separately from the ventral aspect of the aorta, which were situated approximately 17 mm apart from each other. The proximal one which was known as the gastro splenic trunk, divided into the left gastric and the splenic arteries, whereas the distal trunk which was known as the hepato mesenteric trunk divided into the common hepatic artery and the superior mesenteric artery. The common hepatic artery ran anterior to the portal vein. This anomalous pattern conformed to the Adachi type V, which is a very rare anomaly and it could be attributed to the developmental changes which occurred in the primitive ventral splanchnic arteries. This rare anomaly could cause a catastrophe during surgical procedures, especially laparoscopic ones, if the same was not kept in mind before contemplating pre -operative investigations. So, the reporting of such a rare case is significant.